Evaluation of agreement levels between parents and children in reporting child oral health-related quality of life in 8-10 year-old children in Isfahan - Parvin Khadem; Seyed Ebrahim Jabarifar; Sosan Sadeghian; Elham Sadat Benandeh; Mohammad Safaie (Isfahan University of Medical Sciences, 2012)
AbstractIntroduction: Oral health includes healthy mouth and its healthy tissues, which prepares us for daily activities without discomfort and dissatisfaction. In this research, agreement level between parents and children aged 8-10 in rating child oral health-related quality of life was studied in Isfahan. Materials and methods: In this descriptive, analytical and cross-sectional study 138 pairs of parents and children aged 8-10 were selected with simple random sampling technique from elementary schools in Isfahan and were asked to complete the relevant questionnaires. The questionnaires evaluated quality of life in four fields of oral signs, functional deficits, and emotional and social health. In order to evaluate child-parent agreement, intra-correlation coefficient (ICC), Pearson's correlation coefficient, Spearman's correlation coefficient and intra-class correlation coefficient (ICC) were used. Results: The agreements between PPQ8-10 (parent perception questionnaire), CPQ8-10 (child perception questionnaire) and the related fields were 0.63, -0.28, and -0.67. The highest agreement level (ICC = 0.69) was related to functional deficits (good), followed by oral signs (ICC = 0.56) (moderate) and emotional health (ICC = 0.31) (mild). The least agreement level was related to social health (ICC = 0.08). Pearson's test showed significant correlations between CPQ8-10 and PPQ8-10 (r = 0.46) (p value < 0.01). Conclusion: Although parents, especially mothers, may be used as proxies for their children in relation to quality of life and related fields, the views of both should be obtained in order to fully represent child oral health-related quality of life issues. Key words: Malocclusion, Parents, Quality of life, Tooth enamel hypoplasia.